Effect of picroside II on erythrocyte deformability and lipid peroxidation in rats subjected to hind limb ischemia reperfusion injury - Çomu FM; Kılıç Y; Özer A; Kirişçi M; Dursun AD; Tatar T; Zor MH; Kartal H; Küçük A; Boyunağa H; Arslan M (Dove Medical Press, 2016)
Faruk Metin Çomu,1 Yiğit Kılıç,2 Abdullah Özer,2 Mehmet Kirişçi,3 Ali Doğan Dursun,4 Tolga Tatar,2 Mustafa Hakan Zor,2 Hakan Kartal,2 Ayşegül Küçük,5 Hakan Boyunağa,6 Mustafa Arslan71Department of Physiology, Kirikkale University Medical Faculty, Kirikkale, 2Department of Cardiovascular Surgery, Gazi University Medical Faculty, Ankara, 3Department of Cardiovascular Surgery, Necip Fazil State Hospital, Kahramanmaras, 4Department of Physiology, Ankara University Medical Faculty, Ankara, 5Department of Physiology, Dumlupinar University Medical Faculty, Kütahya, 6Department of Biochemistry, Kirikkale University Medical Faculty, Kirikkale, 7Department of Anaesthesiology and Reanimation, Gazi University Medical Faculty, Ankara, TurkeyBackground: Ischemia reperfusion injury (I/R) in hind limb is a frequent and important clinical phenomenon. Many structural and functional damages are observed in cells and tissues in these kinds of injuries. In this study, we aimed to evaluate the effect of picroside II on lipid peroxidation and erythrocyte deformability during I/R in rats.Methods: Rats were randomly divided into four groups – each containing six animals (sham, I/R, sham + picroside II, and I/R + picroside II). The infrarenal section of the abdominal aorta was occluded with an atraumatic microvascular clamp in I/R groups. The clamp was removed after 120 minutes and reperfusion was provided for a further 120 minutes. Picroside II (10 mg·kg-1) was administered intraperitoneally to the animals in the appropriate groups (sham + picroside II, I/R + picroside II groups). All rats were euthanized by intraperitoneal administration of ketamine (100 mg·kg-1) and taking blood from the abdominal aorta. Erythrocytes were extracted from heparinized complete blood samples. Buffer (PT) and then erythrocytes (PE) were passed through the filtration system and the changes in pressure were measured to investigate the role of serum malondialdehyde and nitric oxide (NO) in lipid peroxidation and erythrocyte deformability index.Results: Deformability index was significantly increased in the I/R group compared to groups sham, sham + picroside-II, and I/R + picroside-II (P<0.0001, P<0.0001, and P=0.007). Malondialdehyde (MDA) and NO levels were evaluated. MDA level and NO activity were also higher in the I/R group than in the other groups. Picroside II treatment before hind limb I/R prevented these changes.Conclusion: These results support that deformability of erythrocytes is decreased in I/R injury and picroside II plays a critical role to prevent these alterations. Further experimental and clinical studies are needed to evaluate and clarify the molecular mechanisms of action and clinical importance of these findings.Keywords: hind limb ischemia reperfusion injury, lipid peroxidation, malondialdehyde, nitric oxide, erythrocyte deformability, picroside II